2012
DOI: 10.1099/mic.0.059824-0
|View full text |Cite
|
Sign up to set email alerts
|

PhpA, a tyrosine phosphatase of Myxococcus xanthus, is involved in the production of exopolysaccharide

Abstract: Protein-tyrosine phosphorylation plays a significant role in multiple cellular functions in bacteria. Bacterial tyrosine phosphatases catalyse the dephosphorylation of tyrosyl-phosphorylated proteins. Myxococcus xanthus PhpA shares homology with DNA polymerase and histidinol phosphatase family members. Recombinant His-tagged PhpA requires Mn 2+ or Co 2+ for phosphatase activity, and shows strict specificity for phosphorylated tyrosine residues. The k m values of PhpA for p-nitrophenyl phosphate (pNPP) and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…S1C to D in the supplemental material). In support of these findings, Kimura and colleagues reported that a ⌬phpA mutant has a hyperagglutination phenotype (21).…”
Section: Genetic Screensupporting
confidence: 54%
See 1 more Smart Citation
“…S1C to D in the supplemental material). In support of these findings, Kimura and colleagues reported that a ⌬phpA mutant has a hyperagglutination phenotype (21).…”
Section: Genetic Screensupporting
confidence: 54%
“…The PhpA protein has been biochemically shown to function as a tyrosine phosphatase and, in a physiological context, is involved in exopolysaccharide (EPS) regulation, because a phpA mutant overexpresses EPS (21). Because EPS is required for S-motility (22), we tested the ⌬phpA mutant for S-motility defects in a strain that lacks A-motility (A Ϫ ).…”
Section: Genetic Screenmentioning
confidence: 99%
“…6B, D, and F). The calculated K m and V max values for BceD His (0.52 Ϯ 0.19 mM and 5.9 Ϯ 0.66 mol min Ϫ1 mg Ϫ1 , respectively), BCAM0208 His (0.27 Ϯ 0.08 mM and 6.7 Ϯ 0.6466 mol min Ϫ1 mg Ϫ1 , respectively) and BCAL2200 His (0.43 Ϯ 0.15 mM and 8.5 Ϯ 0.7666 mol min Ϫ1 mg Ϫ1 , respectively) were similar for all three enzymes and also within the range reported for other prokaryotic phosphatases (63)(64)(65).…”
Section: Bcal2200 But Not Bced or Bcam0208 Is Tyrosine Phosphorylatedsupporting
confidence: 58%
“…Remarkably, BCAM0208, BceD, and BCAL2200 display similar kinetic parameters in vitro, as was also found with other bacterial tyrosine phosphatases (63)(64)(65). However, only BCAL2200 was required for the optimal growth of B. cenocepacia in minimal medium, suggesting that its function is particularly important for adaptation to nutrient starvation.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, biochemical analyses demonstrated that SMc02309 is able to hydrolyse the artificial substrate p-NPP, a commonly used substrate in phosphatase assays in vitro (Bennett et al, 2001;Mori et al, 2012;Standish & Morona, 2014 obtained for SMc02309 were similar to those described for the LMW-PTP BceD of Burkholderia cepacia (Ferreira et al, 2007), the Wzb of Acinetobacter iwoffii (Nakar & Gutnick 2003), the Yor5 of Klebsiella pneumoniae (Preneta et al, 2002), the Wzb of E. coli (Vincent et al, 1999) and the Ptp of Acinetobacter johnsonii (Grangeasse et al, 1998). In addition, the optimal pH and temperature for catalytic activity resemble those for the above-mentioned bacterial Cysbased protein phosphatases.…”
Section: Discussionmentioning
confidence: 99%